Extraction of soil nitrogen by chloroform fumigation – A new index for the evaluation of soil nitrogen supply - Yu, Wantai; Brookes, Philip C.; Ma, Qiang; Zhou, Hua; Xu, Yonggang; Shen, Shanmin (Soil biology & biochemistry, 2011)
The N extracted after chloroform (CHCl 3) fumigation was determined as a possible index of soil N supply to plants. The relationships between extractable N following fumigation and reference indices such as total N, alkali-hydrolyzable N, N released by the Stanford short-term incubation method, and the N extracted by KCl and by CaCl 2, were measured in nine soils of differing soil N supply capacity. A highly significant correlation was achieved between the extractable N released by fumigation and the N released by the Stanford method, i.e. a short-term aerobic incubation ( r = 0.87). Similarly, the correlation between extractable N by fumigation and the N uptake by ryegrass was highly statistically significant ( r = 0.93). Using the N extracted following fumigation has the advantage that laboratory results are available in two days and are both reproducible and of high precision. Therefore, the N extracted following fumigation is a valid, timesaving and precise index of soil N supply capacity. ► Significant correlation: N released by Stanford method and CHCl 3 fumigation. ► Significant correlation: extractable N by fumigation and ryegrass N uptake. ► The N extracted following fumigation is a valid index of soil N availability.